Protein–polysaccharide biosynthesis. Membrane-bound saccharides - Derge, Jeffery G. (1972)
Membrane-bound saccharides obtained from ear cartilage from rabbits recovering from papain injection were examined for glycosyl acceptor properties, alkali lability, molecular size and degree of sulphation. Although considerable glucuronosyl transfer from UDP-glucuronic acid could be demonstrated, less than one-third could be identified as representing chondroitin linkage formation; there was little or no effect of molecular size on acceptor properties. Approximately one-half of the membrane-associated chondroitin-like saccharide chains are solubilized by alkali, whereas one-half require proteolysis for solubilization. These fractions are analytically indistinguishable and both contain xylose and galactose as well as uronic acid and sulphated N-acetyl-galactosamine. All fragments that were examined contained stoicheiometric amounts of axial sulphate ester, strongly suggesting a close relationship between chain extension and sulphation.